PROSES MORFOLOGIS JENAMA KOSMETIK KOREA BERBAHASA PRANCIS - Rosiana, Agnes Andryani; Pratama, Dian Agustina; Satiakemala, Silvi (JURNAL ILMU BUDAYA, 2023)
This study aims to describe the morphological process of South Korean cosmetics brand names in French. The data of this study are South Korean cosmetic brand commonly found in shopping centers (malls) and online shopping applications (e-commerce). The instrument used in this study was the human instrument or the researcher himself based on the theory of word formation in French. The data is then collected, grouped and analyzed. The results showed that there were several brands of South Korean cosmetics in French that were circulating in the community. In writing South Korean cosmetics brands are vulnerable to brands that are not in accordance ortographic and grammar in French.